Implementasi Aplikasi SISFOANGUD dalam Mendukung Efisiensi Kerja Petugas Informasi di Bandara Sultan Muhammad Salahuddin Bima - Preti Sinta; Amelia Puspa Tamara (Ebisnis Manajemen, 2025)
SISFOANGUD is an operational data reporting apllication developed by the Ministry of Transportation to digitalize work processes in the air transportation sector. This study aiims to analyze the implementation of SISFOANGUD (Sistem Informasi Angkutan Udara) in supporting the work efficiency of information Unit officers at Sultan Muhammad Salahuddin in Bima. The underlying issue of this research is thet information unit staff still tend to rely on manual recording, one habit that persists is writing data ob small pieces of paper first before inputting it into the application. The research employed a descriptive qualitative method, with data collected through observation, interviews, documentation, and self appraisal. The data analysis technique used was thematic analysis, with data validity tested through source and technique trianggulation. The results of the study show that the SISFOANGUD application can support the work effiency of Information Unit officers if it is used consistently, supported by clear standard operating prosedures (SOP), continuous training, a shift in work culture toward digital systems, and increased self awareness among staff.